2019
DOI: 10.3390/agronomy9030127
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Soil Microbes to Improve Plant Phosphate Efficiency in Cropping Systems

Abstract: Phosphorus is an essential macronutrient required for plant growth and development. It is central to many biological processes, including nucleic acid synthesis, respiration, and enzymatic activity. However, the strong adsorption of phosphorus by minerals in the soil decreases its availability to plants, thus reducing the productivity of agricultural and forestry ecosystems. This has resulted in a complete dependence on non-renewable chemical fertilizers that are environmentally damaging. Alternative strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 163 publications
(190 reference statements)
0
24
0
1
Order By: Relevance
“…Over the past two decades, significant advances have been made in elucidating the molecular signaling mechanisms required for AM fungi to colonize plants (Kamel et al, 2017;Luginbuehl and Oldroyd, 2017;MacLean et al, 2017;Choi et al, 2018). In brief, low phosphorus availability in the soil leads to reduced phosphorus levels within plant tissues (Kafle et al, 2019). This deficiency triggers increased biosynthesis of strigolactones, a class of plant hormones that also function as signaling molecules for AM fungi (Akiyama and Hayashi, 2006;Yoneyama et al, 2007;Gomez-Roldan et al, 2008;Umehara et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, significant advances have been made in elucidating the molecular signaling mechanisms required for AM fungi to colonize plants (Kamel et al, 2017;Luginbuehl and Oldroyd, 2017;MacLean et al, 2017;Choi et al, 2018). In brief, low phosphorus availability in the soil leads to reduced phosphorus levels within plant tissues (Kafle et al, 2019). This deficiency triggers increased biosynthesis of strigolactones, a class of plant hormones that also function as signaling molecules for AM fungi (Akiyama and Hayashi, 2006;Yoneyama et al, 2007;Gomez-Roldan et al, 2008;Umehara et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous microorganisms, including fungi, are capable of releasing P from soil through solubilization and mineralization in the natural soil environment (Alori et al, 2017;P. N. Bhattacharyya & Jha, 2012;Kafle et al, 2019). It is estimated that 50% of all bacteria in soil are capable of solubilizing P (S. B.…”
Section: The Diversity Of P Solubilizing Rhizbacteriamentioning
confidence: 99%
“…According to Alori et al, 2017, organic P can be as high as 30 -50% of the total P in soil. The most common form of organic P is phytate/inositol P but are largely unavailable to plants because they lack phytase activities (Alori et al, 2017;Kafle et al, 2019;A. Kumar, 2016).…”
Section: Mechanisms Of P Solubilizing Plant Root Residing Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial combination effects of bacteria with fungi have been reported by Patreze and Cordeiro (2004) who found that these bacteria may affect fungi and plant host through different mechanisms that affect receptivity of root, root-fungus recognition, fungal growth, modification of chemistry for rhizospheric soil, and germination of the fungal propagules. Kafle et al, (2019) reported that Arbuscular Mycorrhizal Fungi and phosphate-solubilizing bacteria have a major role in natural and agro-ecosystems, and their use as bioinoculants is an increasing tendency in agricultural practices.…”
Section: Introductionmentioning
confidence: 99%